The Synergistic Effects of Sonication and Microwave Processing on the Physicochemical Properties and Phytochemicals of Watermelon (Citrullus lanatus) Juice - Maham Navida; Muhammad Nadeem; Tahir Mahmood Qureshi; Rami Adel Pashameah; Faiqa Malik; Aqsa Iqbal; Muhammad Sultan; Hala M. Abo-Dief; Abdullah K. Alanazi (Agriculture, 2022)
In recent years, consumers have increasingly demanded nutritious, healthy, and fresh-like food products with high organoleptic quality. Watermelon is rich in water, which is 92% mandatory for body functioning, and contains several vitamins, amino acids, antioxidants, carotenoids, and lycopenes with various health benefits. The present study examines the combined effect of ultrasound (US) and microwave (MW) on the physico-chemical and phytochemicals of watermelon juice during storage (up to 120 days). Sonication was employed for different time intervals, particularly from 2 to 8 min at 20 kHz frequency and 525 W power, while microwave was applied at two different time intervals (1 min 50 s and 2 min) at 1000 W power and a frequency of 2450 MHz. The product was stored at 4 °C up to 120 days for further examination. Our results revealed that treatment T5 (10 min ultrasound & 1 min 50 s microwave) manifested the maximum cloud value (3.00), acidity (0.15%), vitamin C content (202.67 mg/100 mL), phenolics (852.57 mgGAE/100 mL), flavonoids (1970.9 µg CE/100 mL), and total antioxidant activity (8650.3 µg equivalent of ascorbic acid/mL of juice). Sonication in combination with microwave proved to be an efficient technique for increasing the antioxidant potential of watermelon juice. Thus, US and MW treatments may be incorporated for enhancing the phytochemical release and shelf life of watermelon juice.